The Experiences about the Symptoms which Experienced Among the Patients With COVID-19 at Tidar 1 Adventist Church Surabaya - Widiani, Priska Ratri; Djula, Sapti H. Widyarti (8ISC Proceedings: Covid-19, 2022)
Coronavirus is a large family of viruses that cause disease in humans and animals. In humans, this virus usually causes respiratory tract infections, ranging from the common cold to the serious illness Severe Acute Respiratory Syndrome. Mild symptoms of uncomplicated acute upper respiratory tract infection may be accompanied by a fever above 38°C, fatigue, shortness of breath, cough, anorexia, malaise, sore throat, anosmia, ageusia, nasal congestion, or headache. Qualitative research method with closed interview techniques to 10 informants and types of audio data. The results of the study are that the process of contracting is mostly in the office and family; the symptoms felt are mostly anosmia and ageusia. The early symptoms of infection are mostly fever and anosmia, and the next symptoms usually take about 2 to 14 days to feel advanced symptoms. The mild symptoms are mostly flu, fever, and ageusia, the most severe symptoms are shortness of breath and anosmia. The symptoms begin to feel better in a few days; it usually takes 2-14 days to recover from the symptoms, and the most difficult symptoms are mostly anosmia, shortness of breath, cough, flu, ageusia, and myalgia. It is expected that further researchers will develop this research with quantitative methods and a larger sample of COVID-19 survivors. Keywords : Coronavirus, COVID-19 Symptoms, Experiences